Two new species of the genus Temnaspis Lacordaire, 1845, (Coleoptera: Chrysomeloidea: Megalopodidae) from China and Myanmar, with notes on the biology of the genus - Li, Kaiqin; Liang, Zongli; Liang, Hongbin (Zootaxa, 2013)
Two new species of the genus Temnaspis Lacordaire, 1845, family Megalopodidae, are described from China and Myanmar: Temnaspis puae Li & H.B. Liang, sp. nov., Temnaspis syringa Li & H.B. Liang, sp. nov. Biological notes are provided for Temnaspis syringa. Temnaspis flavicornis Jacoby, 1892 is redescribed and a lectotype designated. A key to species of the genus Temnaspis with black elytra in China and adjacent areas is provided.